Antimicrobial Action of Compositions Based on Thiosulfonates and Biosurfactants on Phytopathogens - Shvets, Volodumur; Karpenko, Olena; Karpenko, Ilona; Novikov, Volodymyr; Lubenets, Vira (Innovative Biosystems and Bioengineering, 2017)
Background. The development of environmentally safe preparations with antimicrobial activity on microorganism-phytopathogens. Objective. Determination of antimicrobial activity of compositions alilthiosulfonate (ATS) and metylthiosulfonate (MTS) with surface-active rhamnolipid biocomplex (RBC) on phytopathogens Agrobacterium tumefaciens and Сlavibacter michiganensis. Methods. Investigation in vitro of antimicrobial activity of compositions based on thiosulfonates and rhamnolipid biocomplex on microorganism-phytopathogens A. tumefaciens and C. michiganensis in accordance with the minimum inhibitory concentration and minimum bactericidic concentrations of developed compositions. Studies of biosurfactant effect on permeability of cell membraines. Results. It is shown that the composition of methyl- and alilthiosulfanilates with RBC are more activе and have lower values of minimum inhibitory and bactericidic concentrations than ATS and MTS alone – on average by 50 %. Conclusions. The results showed the prospects of rhamnolipid-biosurfactants use for creation of highly effective compositions with biocides for plant protection.